Barriers and facilitators to best care for idiopathic pulmonary fibrosis in Australia. Issue 1 (15th November 2021) - Tikellis, Gabriella; Corte, Tamera J.; Teoh, Alan K.Y.; Glaspole, Ian N.; Macansh, Sacha; Holland, Anne E.
Abstract: Background and objective: In Australia, little is known about delivery of care for people with idiopathic pulmonary fibrosis (IPF). This study examined the organization of IPF care across Australia, how it aligns with guidance for best practice, and identified barriers and facilitators to best care. Methods: Data on the organization of IPF care in Australia were collected from public hospitals using a study‐specific questionnaire between February and July 2020. Semi‐structured telephone interviews were conducted with respiratory physicians from around Australia between April and December 2020. Interviews were transcribed verbatim and thematic analysis was undertaken. Results: Almost all hospitals ( n  = 38, 97%) held multidisciplinary meetings (MDMs) for diagnosing IPF, with 90% of multidisciplinary teams including expert respiratory physicians and radiologists; however, rheumatologists, interstitial lung disease nurses and a histopathologist were often not available. More than 90% of institutions had access to oxygen therapy, pulmonary rehabilitation and advanced care planning, but access to psychological support and clinical trials was limited (53% and 58%, respectively). Fifteen respiratory physicians (27% regional) were interviewed. Approaches to diagnosis, treatment and access to referral services were generally consistent with best practice guidance; however, regional respondents reported barriers related to inadequate staffing, lack of a nurse coordinator, inadequate access to clinical trials and funding models. Telehealth technologies were perceived as facilitators to best care. Conclusion: Clinical management of IPF in Australia generally aligns with best practice guidance, but there may be some inequity of access to specialist services, particularly in regional areas, that should be addressed to ensure optimal care for all. Abstract : Specialist services for the diagnosis and care of patients with idiopathic pulmonary fibrosis (IPF) are available across Australia and generally align with best practice guidance. Telehealth technologies were perceived as facilitators of best care, but inequities in access to services for patients with IPF in regional areas remained.